A bibliometric analysis of research into internet gaming disorders in Korea - Zhang, Melvyn (2023)
After the concept of "Internet addiction" was first proposed in 2004, "Internet gaming disorder" (IGD) was included in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as a disorder requiring further research. IGD is prevalent in South Korea, and many studies have been conducted on the disorder. Previous studies have helped in understanding various aspects of IGD, but a comprehensive understanding of the research trends is required to identify research gaps. Therefore, we conducted a bibliometric review of all published IGD studies in South Korea. For the identification of articles, the Web of Science database was used. Data analysis was performed using Biblioshiny. A total of 330 publications were included in the analysis. The average number of citations per document was 17.12. These publications were written by a total of 658 authors, and the number of coauthors per document was 5.07. The years with the most publications were 2018 (n = 57), 2017 (n = 45), and 2019 (n = 40). The top three journals containing publications were the Journal of Behavioral Addictions (n = 46), Frontiers in Psychiatry (n = 19), and Psychiatry Investigation (n = 14). In a keyword analysis (apart from "IGD", "internet addiction", and "addiction"), the keywords "adolescent" (n = 31), "self-control" (n = 11), and "impulsivity" (n = 11) were included. T. This bibliometric analysis explores and summarizes the publications on IGD in South Korea. The results are expected to provide researchers with insights for further studies into IGD.